Lutas e escolas de ofício: analisando o judô brasileiro - Drigo, Alexandre Janotta [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2009)
This lecture, presented in IV SEPEF, has origin in studies developed about diferent points of view, approaching the martial arts, combat sports or fights. The grand question of analysis was the judo, where many elements presented, as leads corporations of brazilian desportes documents, Olympic athletes performance and speechs produced by fights agents allowd a reflection about the relationship between the artesanal formation of black-belt and the academic formation in Physical Education, in the ambit of this modality.

Esta palestra, apresentada no IV SEPEF, foi oriunda de estudos desenvolvidos a partir de diversas óticas, abordando as artes marciais, esportes de combates ou lutas. O principal objeto de análise foi o judô, onde vários elementos apresentados, como documentos de entidades dirigentes do desporto no Brasil, desempenho dos atletas Olímpicos e discursos produzidos por representantes da lutas permitiram refletir sobre a relação entre a formação artesanal do faixa-preta e a formação acadêmica em Educação Física, no âmbito desta modalidade.
Figths and office schools: analyzing the brazilian judo
Keywords: Judo; Office schools; Profession